AB0295 CHANGE IN DISEASE ACTIVITY AND TREATMENT RESPONSE AFTER ABATACEPT TREATMENT FOR RHEUMATOID ARTHRITIS: REAL-WORLD EVIDENCE FROM THE UK. (2nd June 2020) - Henning, S.; Groves, L.; Hurst, M.; Sugrue, D.; Gordon, J.; Choy, E.
Abstract : Background: Patients with moderate to severe active rheumatoid arthritis (RA) may be treated with biological disease-modifying antirheumatic drugs (bDMARDs), such as abatacept, after treatment failure with conventional synthetic DMARDs (csDMARDs). Abatacept has shown equivalent efficiency with other targeted therapies for RA in clinical trials and network meta-analyses. However, there is limited real-world evidence on patient outcomes associated with abatacept treatment in UK routine clinical practice. Objectives: To describe the clinical outcomes of RA patients treated with abatacept in UK real-world clinical practice. Methods: A multi-centre, retrospective observational study was undertaken in RA patients treated with abatacept at any line of therapy (LOT). Data were extracted from medical records at four UK hospitals. Patients aged 18 years or older who received abatacept between 1 January 2013 and 31 December 2017 were included. The index date was the date of first bDMARD initiation, with follow-up from index date to latest RA clinic visit, death or 31 December 2017, whichever occurred first. Clinical outcomes (disease activity and response to treatment) were measured using the 28-joint Disease Activity Score based on erythrocyte sedimentation rate (DAS28-ESR) and European League Against Rheumatism (EULAR) response criteria 1-3 . Results: The study included 213 patients (mean age 55.2 years, 71.4% female, 7.0 years mean duration of RA at index date). Where ACPA and RF status were recorded, 66.1% of patients were anti-citrullinated protein antibodies (ACPA) and rheumatoid factor (RF) positive at index. Mean DAS28-ESR at index was 6.2 (SD 1.0) and 80.9% of patients were categorised with high disease activity. Irrespective of LOT, changes in DAS28-ESR (where recorded) from LOT initiation among patients treated with abatacept versus other bDMARDs were -1.59 vs -1.56 (LS mean (SE): -0.04; 95% CI: -0.45, 0.38; p=0.86) at 6 months and -1.98 vs -1.42 (LS mean (SE): -0.56; 95% CI: -1.04, -0.07; p=0.03) at 12 months, respectively. Table 1 shows that compared with other bDMARDs, patients treated with abatacept at any LOT experienced good response to treatment at 6 months (22.8%, n= 21/92 vs 15.9%, n= 24/151) and 12 months (27.9%, n= 17/61 vs 20.5%, n= 24/117) according to EULAR criteria. Patients who received abatacept remained on treatment for significantly longer than patients who received other bDMARDs at LOT1 (median 53.4 vs 17.4 months; p<0.01) (Figure 1 ) and at LOT2 (median 40.1 vs 17.1 months; p<0.01). Conclusion: RA patients who received bDMARDs, including abatacept, experienced reduced disease activity. These findings are comparable with those from a European, multicentre, observational study on patients receiving abatacept 4 . The mechanisms associated with such clinical benefit should be elucidated in future research. References: [1]Prevoo et al. Arthritis Rheum 1995;38:44–8. [2]Fransen & van Riel. Clin Exp Rheumatol 2005;23:S93–9. [3]van Gestel et al. Arthritis Rheum 1998;41:1845–50. [4]Alten et al. Clin Rheumatol (2019) 38: 1413. Acknowledgments: Yusuf Patel Srinivasan Venkatachalam James Maxwell Usman Farooqui Kevin Pollock Disclosure of Interests: Sadie Henning Shareholder of: Sadie Henning is a shareholder for Bristol-Myers Squibb Pharmaceuticals Ltd., Employee of: Sadie Henning is employed by Bristol-Myers Squibb Pharmaceuticals Ltd., Lara Groves Grant/research support from: Lara Groves is an employee of Health Economics and Outcomes Research Ltd., Cardiff, UK, who received fees from Bristol-Myers Squibb Pharmaceuticals Ltd in relation to this study., Michael Hurst Grant/research support from: Michael Hurst is an employee of Health Economics and Outcomes Research Ltd., Cardiff, UK, who received fees from Bristol-Myers Squibb Pharmaceuticals Ltd in relation to this study., Daniel Sugrue Grant/research support from: Daniel Sugrue is an employee of Health Economics and Outcomes Research Ltd., Cardiff, UK, who received fees from Bristol-Myers Squibb Pharmaceuticals Ltd in relation to this study., Jason Gordon Grant/research support from: Jason Gordon is an employee of Health Economics and Outcomes Research Ltd., Cardiff, UK, who received fees from Bristol-Myers Squibb Pharmaceuticals Ltd in relation to this study., Ernest Choy Grant/research support from: Amgen, Bio-Cancer, Chugai Pharma, Ferring Pharmaceuticals, Novimmune, Pfizer, Roche, UCB, Consultant of: AbbVie, Amgen, AstraZeneca, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Chelsea Therapeutics, Chugai Pharma, Daiichi Sankyo, Eli Lilly, Ferring Pharmaceuticals, GlaxoSmithKline, Hospita, Ionis, Janssen, Jazz Pharmaceuticals, MedImmune, Merck Sharp & Dohme, Merrimack Pharmaceutical, Napp, Novartis, Novimmune, ObsEva, Pfizer, R-Pharm, Regeneron Pharmaceuticals, Inc., Roche, SynAct Pharma, Sanofi Genzyme, Tonix, UCB, Speakers bureau: Amgen, Boehringer Ingelheim, Bristol-Myers Squibb, Chugai Pharma, Eli Lilly, Hospira, Merck Sharp & Dohme, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Roche, Sanofi-Aventis, UCB